2020
DOI: 10.1001/jamaoncol.2020.1634
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of Definitions of Hyperprogressive Disease During Immunotherapy for Non–Small Cell Lung Cancer

Abstract: Question Are the different definitions used to assess hyperprogressive disease during immunotherapy for non-small cell lung cancer representative of the same tumoral behavior? Findings For this multicenter cohort study of 406 patients with advanced non-small cell lung cancer treated with programmed cell death 1/programmed cell death 1 ligand inhibitors, the 5 disease definitions assessed resulted in diverse incidences, different patient characteristics, and different associations with survival outcomes. A new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 20 publications
2
77
0
2
Order By: Relevance
“…When using the second method for evaluation of tumor growth (ΔTGR) as previously proposed [ 11 ], we found a statistically difference in PFS between hyperprogressors and non-hyperprogressors (median PFS 1.8 months (95% CI, 1.51–2.08) vs. 3.1 months (95% CI, 1.29–4.90) respectively, p = 0.002), but no difference in OS (median OS 11.06 (95 % CI, 0–22.58) in patients with HPD vs. 12.53 months (95% CI, 8.27–16.78) in patients with non-HPD, p = 0.674).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When using the second method for evaluation of tumor growth (ΔTGR) as previously proposed [ 11 ], we found a statistically difference in PFS between hyperprogressors and non-hyperprogressors (median PFS 1.8 months (95% CI, 1.51–2.08) vs. 3.1 months (95% CI, 1.29–4.90) respectively, p = 0.002), but no difference in OS (median OS 11.06 (95 % CI, 0–22.58) in patients with HPD vs. 12.53 months (95% CI, 8.27–16.78) in patients with non-HPD, p = 0.674).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Kato et al and Matos et al used a mixture of clinical and radiological criteria by incorporating TTF < 2 months in HPD definition [ 21 , 22 ]. In an attempt to comprehensively compare and unify different definitions of HPD, Kas et al analyzed all methodologies of previous HPD definitions and applied them to a cohort of patients with NSCLC [ 11 ]. Interestingly, the authors observed several differences in the rate of HPD depending on the method used; in addition, they showed that only a minority of patients (4.7%) were covered by all definitions, suggesting that each methodology includes a distinct subgroup of patients with diverse patterns of tumor progression [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, it has been suggested that irAEs could help select responders to ICB in bladder cancer (17). Secondly, some patients experience an acceleration of tumor growth kinetics with poor survival called hyperprogression which, at present, remains difficult to characterize (18,19).…”
Section: Characterizing the Immune Function In The Response To Checkpmentioning
confidence: 99%